2019
DOI: 10.3390/ijns5020018
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Selected Disorders in Nepal: A Pilot Study

Abstract: The prevalence of metabolic disorders in Nepal is yet unknown, although many case reports occur in literature. Heel-prick blood samples from newborns were collected on Dried Blood Spot (DBS) collection cards and tested through Tandem Mass Spectroscopy and fluorescence assays for disorders included in the Swiss neonatal screening program; two cases of hypothyroidism and one case of cystic fibrosis were identified. Thyroid stimulating hormone (TSH), immuoreactive trypsinogen (IRT), hydroxyprogesterone (OHP), tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
2
7
0
1
Order By: Relevance
“…Similarly, hypothyroidism has been reported in several studies [72] and is acknowledged as a treatable health problem in Nepal. A pilot study on neonatal screening conducted in Nepal found a prevalence of hypothyroidism of 1in 2180 [72].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Similarly, hypothyroidism has been reported in several studies [72] and is acknowledged as a treatable health problem in Nepal. A pilot study on neonatal screening conducted in Nepal found a prevalence of hypothyroidism of 1in 2180 [72].…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, hypothyroidism has been reported in several studies [72] and is acknowledged as a treatable health problem in Nepal. A pilot study on neonatal screening conducted in Nepal found a prevalence of hypothyroidism of 1in 2180 [72]. Most of the South Asian countries like Bangladesh, India, Sri Lanka and Pakistan have initiated newborn screening for hypothyroidism [79].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Важливе значення мають профілактичні програми, які застосовуються у новонароджених і мають на меті виділення групи ризику для подальшого обстеження і лікування. Це так званий масовий неонатальний скринінг, якому підлягають всі новонароджені [13,36].…”
unclassified